Inspiring and Preparing Our Future Leaders: Evaluating the Impact of the Early Career Women’s Leadership Program - Lee JK; Tackett S; Skarupski KA; Forbush K; Fivush B; Oliva-Hemker M; Levine RB (Dove Medical Press, 2024)
Jennifer K Lee,1- 3 Sean Tackett,4,5 Kimberly A Skarupski,2,4,6 Kathy Forbush,7 Barbara Fivush,2,3 Maria Oliva-Hemker,2,3 Rachel B Levine2,4 1Department of Anesthesiology and Critical Care Medicine, Johns Hopkins University School of Medicine (JHU), Baltimore, MD, USA; 2Office of Faculty, JHU, Baltimore, MD, USA; 3Department of Pediatrics, JHU, Baltimore, MD, USA; 4Department of Medicine, JHU, Baltimore, MD, USA; 5Biostatistics, Epidemiology, and Data Management Core, JHU, Baltimore, MD, USA; 6Bloomberg School of Public Health, JHU, Baltimore, MD, USA; 7Human Resources, Office of Talent Management, JHU, Baltimore, MD, USACorrespondence: Jennifer K Lee, Email Jennifer.lee@jhmi.eduPurpose: The number of women in high-level leadership in academic medicine remains disproportionately low. Early career programs may help increase women's representation in leadership. We evaluated the Early Career Women's Leadership Program (ECWLP). We hypothesized that participants would rate themselves as having increased confidence in their leadership potential, improved leadership skills, and greater alignment between their goals for well-being and leading after the program. We also explored the participants' aspirations and confidence around pursuing high-level leadership before and after the program.Methods: We surveyed women physicians and scientists before and after they participated in the 2023 ECWLP, consisting of 11 seminars over six months. We analyzed pre- and post-program data using Wilcoxon signed-rank tests. We analyzed answers to open-ended questions with a content analysis approach.Results: 47/51 (92%) participants responded, and 74% answered pre- and post-program questionnaires. Several metrics increased after the program, including women's confidence in their ability to lead (p< 0.001), negotiate (p